Development of a Web-based Application for Offline Mass Registration - Regina Ella Setyandari; Ridwan Sanjaya; Agus Cahyo Nugroho (Soegijapranata Catholic University, 2023)
The emergence of Covid-19 in 2020 has changed many aspects of life in the world. The Covid-19 pandemic has also affected the economy, education and other sectors such as the social and religious fields. Due to restrictions on attending worship activities, the idea emerged to utilize facilities that were believed to assist worship activities. One of facilities contained in existing technology to assist houses of worship is online. The influence of technology during the pandemic on the social and religious sectors is considered to have great benefits. As an example of the impact that occurred in the Church of St. Theresia of the Bongsari Parish.When mid-July 2020, after the government issued a New Normal policy, the Parish began to open mass activities by offline. The system used at that time included people registering through a collective list from the head of section where parishioners domicile nearby. However, the registration system is still considered ineffective, so the registration system is then developed using the Google Form facility. Although the offline mass registration system has undergone many developments, it still has many shortcomings. Therefore, the responsive web-based offline mass registration application is expected to be able to help the problems experienced by the church during the mass registration flow as well as the development of a dashboard as a means to be able to process data easily and efficiently for church administration officers. Application development is carried out using the ADDIE method, namely Analyze, Design, Development, Implementation, and Evaluation. In addition, the Rapid Application Development (RAD) method is also used to support the application development process.In this study, a survey with 60 respondents was carried out with the community, and from the test results it can be concluded that the usefulness of the offline mass registration application, as well as device support and the ease and pleasure of using this application have a correlation with the intention to use a website-based offline mass registration application.